Determination of neutron flux parameters in PUSPATI TRIGA Mark II Research Reactor, Malaysia - I. A., Alnour; H., Wagiran; N., Ibrahim; S., Hamzah; Wee, Boon Siong; M. S., Elias; J. A., Karim (Springer Netherlands, 2013)
In standardization NAA, it is necessary to characterize the neutron spectrum parameters such as epithermal neutron flux shape factor (a), thermal to epithermal neutron flux ratio (f), thermal neutron flux (uth) and epithermal neutron flux (uepi) in the irradiation facility to determine the concentration of an element in the sample using absolute and k0 standardization methods. The a and f were determined using Cd-ratio multi monitor method using experimental data obtained in PUSPATI TRIGA Mark II research reactor at four irradiation positions (10, 20, 30 and 40) of the rotary rack. The calculated values of a and f ranged from 0.006 to 0.0281 and 18.56 to 19.12 respectively. The average values of uth and uepi were found as 2.33 9 1012 and 1.23 9 1011 n cm-2 s-1 respectively. Moreover, a comparison of the neutron flux parameters in the present study shows an acceptable level of consistency with those of previous studies.